El pseudo-arabista Escolano - Barceló, Carme (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: The Valencian historian Gaspar Escolano (XVII century) collects in his Décadas the etymologies of Valenciana names and place-names given by other historians. The author has extracted and ordered them alphabetically.